Masculinity And Power Reflected In Christoper Nolan'sBatman The Dark Knight Rises Movie (2012): A Psychoanalytic Approach - Afni, Ghea Nurfadila, Dr. Phil. Dewi Candraningrum M.Ed, Drs. H. Abdillah Nugroho, M.Hum (2013)
The major problem of this study is to reveal how major characters apply his masculinity and power that they have to survive and shows their existance. The aim of this study is to identify the relationship between the masculinity and power that major character have, using the mean of structural and psychoanalytic analysis. The object of this study is Batman The Dark Knight Rises movie and it is focused on one of the major characters. The benefit of the study is to give some contributions in the application of psychoanalytic approach in literary study and to fulfill the requirement for getting Bachelor Degree in English Department. This study uses library data. The primary data are taken from the movie itself, while the secondary data are taken other material related to the study. The method of data collection is description and the study employs Sigmund Freud's psychoanalysis to answer the problem. The outcome of the study shows the following conclusions. First, based on the structural analysis it is clear that in BatmanThe Dark Knight Rises movie, Christoper Nolan deliver message that masculinity and power is needed in everyone's life because it is important and can influence someone's life to survive in their environment, because someone who has a strength masculinity and power can show who really they are and show their existence. Second, based on the psychoanalytic approach shows that masculinity and power can give effect to people's mind.